ANALISA PENGARUH VARIASI MAIN JET DAN PILOT JET TERHADAP PERFORMANCE MESIN PADA SEPEDA MOTOR - Purwanto Purwanto; Abdul Wahab; Artono Raharjo (Jurnal Teknik Mesin, 2017)
Motor vehicle is a ground transportation that are beneficial to the community for personal and business purposes. Fuel intake system is one that affects engine performance. Carburetor is the fuel intake system, and has a main jet and pilot components jet.Karburator is a tool for mixing fuel with air. Main function is to supply jet fuel to the engine cylinders when the engine in conditions adle round. As well as the pilot jet is used to supply the fuel needs of the appropriate materials at all levels of engine speed and load on the idle rotation speed. The influence of the main jet and pilot jet standards, main jet and pilot jet and main jet small variation and large variation of the pilot jet engine performance include, power, torque, fuel consumption, specific fuel consumption and the effective thermal efficiency effectively. The method is carried out in the laboratory and conduct experimental data using statistical analysis to determine the results of the data. With a 4 stroke motorcycle gasoline. Main jet and pilot jet used in the study is the main jet (72) and pilot jet (38) standard, the main jet (70) and pilot jet (35) small variations, as well as the main jet (75) and pilot jet (40) variations large. With a 3500 rpm engine speed, load 5 kg, and 16 ml of fuel. The resulting torque main jet and pilot jet standards, small variations, as well as a large variety of the same, namely 1.25 (kg.m). The resulting effective power was the same, namely 6.11 (PS) or 6.031 (HP). Fuel consumption resulting from the main jet and pilot jet standard is 0.617 (kg/hour), a small variation produces 0,972 (kg/hour), and fuel consumption resulting large variation 0.483 (kg/hour). Specific fuel consumption resulting main jet and pilot jet standard 0.102 (kg/HP.m), a small variation of 0.161 (kg/HP.m), a large variation is 0.080 (kg/HP.m). As well as the effective thermal efficiencies generated by the main jet and pilot standard is 0.648. The resulting effective thermal efficiency of the main jet and pilot jet and the variation resulting 0.412 kesil main jet and pilot jet large variation 0.828. Main jet and pilot jet large variations are increasing